The calcium ATPase SERCA2 regulates desmoplakin dynamics and intercellular adhesive strength through modulation of PKCα signaling - Hobbs, Ryan P. (Federation of American Societies for Experimental Biology, 2011)
Darier's disease (DD) is an inherited autosomal-dominant skin disorder characterized histologically by loss of adhesion between keratinocytes. DD is typically caused by mutations in sarcoendoplasmic reticulum Ca(2+)-ATPase isoform 2 (SERCA2), a major regulator of intracellular Ca(2+) homeostasis in the skin. However, a defined role for SERCA2 in regulating intercellular adhesion remains poorly understood. We found that diminution of SERCA2 function by pharmacological inhibition or siRNA silencing in multiple human epidermal-derived cell lines was sufficient to disrupt desmosome assembly and weaken intercellular adhesive strength. Specifically, SERCA2-deficient cells exhibited up to a 60% reduction in border translocation of desmoplakin (DP), the desmosomal cytolinker protein necessary for intermediate filament (IF) anchorage to sites of robust cell-cell adhesion. In addition, loss of SERCA2 impaired the membrane translocation of protein kinase C α (PKCα), a known regulator of DP-IF association and desmosome assembly, to the plasma membrane by up to 70%. Exogenous activation of PKCα in SERCA2-deficient cells was sufficient to rescue the defective DP localization, desmosome assembly, and intercellular adhesive strength to levels comparable to controls. Our findings indicate that SERCA2-deficiency is sufficient to impede desmosome assembly and weaken intercellular adhesive strength via a PKCα-dependent mechanism, implicating SERCA2 as a novel regulator of PKCα signaling.—Hobbs, R. P., Amargo, E. V., Somasundaram, A., Simpson, C. L., Prakriya, M., Denning, M. F., Green, K. J. The calcium ATPase SERCA2 regulates desmoplakin dynamics and intercellular adhesive strength through modulation of PKCα signaling.